Analysis of Green Open Space Potential as a Halal Recreation Area with an Urban Morphology Approach (Case Study of Karebosi Field, Makassar City, Indonesia) - Arsyad, Nashrah; Nusran, Muhammad; Said, Juhana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Karebosi Field is one of the green open spaces in Makassar City that attracts many visitors. As one of the green open spaces that functions as a recreation area, Karebosi Field has not fully provided comfort to its visitors. Along with the trend of halal recreation that is starting to be of interest to many people, Karebosi Field has the potential to be developed as a halal recreation area. This study aims to analyze the potential of Karebosi Field as a halal recreation area with a city morphology approach. A scoring analysis method is used to find the potential of Karebosi Field as a halal recreation area based on data obtained through field survey results. The results of this study are to find the potential of Karebosi Field as a halal recreation area with a city morphology approach.